Neoadjuvant Systemic Therapy in Localized and Locally Advanced Renal Cell Carcinoma - Khaleel, Sari; Jiang, Song; Kotecha, Ritesh R.; Hakimi, A. Ari (Frontiers in Urology, 2022)
While the majority of renal cell carcinoma (RCC) cases present at an early stage, a significant number of patients are diagnosed with either locally advanced or metastatic disease. While surgical resection remains the definitive curative management in the localized setting, many patients experience disease relapse and the 5-year recurrence rate following nephrectomy nears 60% for patients with high-risk localized disease. As systemic therapies including anti-angiogenesis, immune checkpoint blockade, and combinations thereof have evolved with dramatic improvements in survival outcomes for patients with metastatic RCC, there is a renewed interest in exploring the utility of these agents in the upfront neoadjuvant and adjuvant setting. Neoadjuvant therapy, administered prior to definitive surgery, aims to eradicate micro-metastatic disease early on and reduce surgical complexity with the overall goals of lowering perioperative morbidity and increasing post-operative recurrence-free and progression-free survival. In this chapter, we present an overview of previously completed and ongoing neoadjuvant systemic therapy clinical trials for patients with localized and locally advanced RCC and discuss potential considerations regarding the utility and future study of neoadjuvant therapy for the optimal management of localized RCC.